Hubungan Kepala Sekolah dalam Manajemen Kurikulum dan Program Pendidikan - Erna Yunita; Pandi Ahmad; Agus Ali (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the relationship between school principals' leadership and the management of curriculum and educational programs in schools. Principals play a strategic role in guiding, coordinating, and developing the curriculum to align with the school's vision, mission, and the needs of students. Through a qualitative descriptive approach based on literature review, this study highlights the importance of principals' managerial competence in planning, implementing, and evaluating the curriculum. The findings indicate that the effectiveness of educational programs, whether intracurricular, co-curricular, or extracurricular, is highly influenced by the principal's ability to manage human resources, facilities, and the school's organizational climate. Thus, good curriculum management under the leadership of the school principal significantly contributes to the overall improvement of education quality. 1) to analyze the role of the principal in curriculum management at the school, 2) to analyze the role of the principal in the implementation of educational programs, 3) to analyze the relationship between the principal's role in curriculum management and the implementation of educational programs at the school, 4) to analyze the factors that affect the effectiveness of the principal in managing the curriculum and educational programs, 5) to analyze how the principal's leadership contributes to the improvement of the quality of educational programs, 6) to analyze the obstacles faced by the principal in managing the curriculum and educational programs.